Ningaloo Marine Park Tourism Scoping Paper - Hopkins, Diane; Wood, David (Curtin Sustainable Tourism Centre, 2006)
The Ningaloo Marine Park extends along a section of the north-west coast of Western Australia. The pocket protects a fringing coral reef that is easily accessible from the shore. The natural beauty of the region and the abundance and variety of marine life draws large numbers of Australian and international tourists. This paper provides an overview of tourism in the Ningaloo region and summarises the characteristics of visitors to the Ningaloo Marine Park, including visitor numbers, place of origin, travel motivations and activities, accommodation, and length of stay. It also outlines the relationship between fishing tourism and other visitor characteristics, and discusses the implications of these findings for the management of the Ningaloo region.This paper is based on primary data from a longitudinal visitor survey of the Ningaloo region conducted between 1997 and 2004. Analysis of the survey data demonstrates that the market segments which visit during the month of April were different from those who choose to visit during other times of the year. For this reason visitor data collected during April is separated from data collected during February, July, and October.